Intravascular imaging in coronary stent restenosis: Prevention, characterization, and management - Abouelnour, Amr; Gori, Tommaso (Frontiers in Cardiovascular Medicine, 2022)
Despite the introduction of drug-eluting stents to combat the neointimal hyperplasia that occurred after BMS implantation, in-stent restenosis is still encountered in a significant number of patients, particularly as increasingly complex lesions are tackled by percutaneous coronary intervention. Many biological and mechanical factors interplay to produce restenosis, some of which are avoidable. Intravascular imaging provided unique insights into various forms of stent-related mechanical issues that contribute to this phenomenon. From a practical perspective, intravascular imaging can therefore help to optimize the stenting procedure to avert these issues. Moreover, once the problem of restenosis eventuates, imaging can guide the management by tackling the underlying identified mechanism. Finally, it can be used to evaluate the re-intervention results. Nevertheless, with the emergence of different treatment options, more evidence is needed to define patient/lesion-specific characteristics that may help to tailor treatment selection in a way that improves clinical outcomes.